EVALUASI POTENSI PELESTARIAN TUNAS HASIL KULTUR IN VITRO DARI TANAMAN OBAT CEPLUKAN (Physalis angulata,L.) - Saepudin Saepudin (Jurnal Ilmiah Farmasi, 2004)
ABSTRACTA tissue culture and plant generation for the ceplukan, Physalis angulata, L has beendeveloped. Callus were efficiently induced on Murashige and Skoog (MS) medium supplementedwith 0,1 ppm indole-3-acetic acid (IAA) and variation of 1, 2, 3, 4, and 5 ppm benzyladenine (BA).The regenerable callus differentiated into shoots. Phytochemical containing of the shoots weredetected and compared with the origin plant using Thin Layer Chromatography (TLC). Flavonoidwas showed by bright blue spot under UV 366 nm and became yellow after smoked by NH3 withHRf 43 and 69. Saponin was showed by yellow spot with HRf 18 and purple spot with HRf 45 aftersprayed by anisaldehyde-sulfuric acid. HRf of the shoots from culture and origin plant were thesame, showed that shoots contains the same phytochemical as the origin plant.Keyword: shoots, tissue culture, restoration, flavonoid, saponin